Threshold values of ankle dorsiflexion and gross motor function in 60 children with cerebral palsy: A cross-sectional study. (4th July 2018) - Rasmussen, Helle M; Svensson, Joachim; Thorning, Maria; Pedersen, Niels W; Overgaard, Søren; Holsgaard-Larsen, Anders
Abstract : Background and purpose — Threshold values defining 3 categories of passive range of motion are used in the Cerebral Palsy follow-Up Program to guide clinical decisions. The aim of this study was to investigate the threshold values by testing the hypothesis that passive range of motion in ankle dorsiflexion is associated with gross motor function and that function differs between the groups of participants in each category. Patients and methods — We analyzed data from 60 ambulatory children (aged 5–9 years) with spastic cerebral palsy. Outcomes were passive range of motion in ankle dorsiflexion with flexed and extended knee and gross motor function (Gait Deviation Index, Gait Variable Score of the ankle, peak dorsiflexion during gait, 1-minute walk, Gross Motor Function Measure, the Pediatric Quality of Life Inventory Cerebral Palsy Module, and Pediatric Outcomes Data Collection Instrument). Results — Significant (p < 0.05) and moderate correlations were documented for range of motion versus Gait Variable Score of the ankle (r = –0.37 and r = –0.37) and range of motion versus peak dorsiflexion (r = 0.49 and r = 0.55). Differences between the groups formed by the categories were shown for Gait Variable Score of the ankle and peak dorsiflexion (p < 0.05). No other significant correlations or differences between the categories were observed. Interpretation — The results suggest that threshold values for ankle dorsiflexion used in the Cerebral Palsy follow-Up Program are of limited clinical value in assessing overall gross motor function, but may be used to identify deviations in ankle-specific gait function.